Mental toughness in coaching: A functional definition determined by elite coaches - Steffen, W.; Woolsey, C.; Quinn, R.; Spradley, B. (The Sport Journal, 2020)
Researchers have explored the mental toughness that is associated with elite athletes as a concept relating to specific activities and sports; however, there is limited research concerning mental toughness among elite coaches. This study expanded previous research by investigating elite coaches` (N=22) perspectives of what attributes were most important for defining mental toughness in coaching. Results of coaching focus groups interviews yielded several themes which were incorporated into a definition of mental toughness of a coach. Mental toughness of a coach is a complex interaction of several characteristics: (1) a determined mindset; (2) resiliency; (3) confidence; and (4) a strong belief in the coach`s system, processes, and actions; all of these characteristics result in consistent behaviors and emotional responses. Coaches were asked to list attributes that they felt were descriptive of the ideal mentally tough coach. Their list included confident, resilient, consistent, positive spirit, energetic, passionate, optimistic, adaptable, possessing inner strength, and patient. These attributes were discussed in consideration of coaches` rationale for these choices. Examining mental toughness can positively assist coaches seeking to become the best they can be.